Evaluation of Pap smear screening history in patients with cervical cancer in Isfahan province during 2014-2016 - Mosayebi, Mahmoud; Tavakolifard, Negah; Sadat Vaezi, Atefeh (Medicinski časopis, 2018)
Abstract Background Absence of regular screening of cervical cancer in Iran and numerous rate of diagnosed cancer in advanced stage show the importance of performing screening. Therefore, the aim of this study was to evaluate Pap smear screening history in patients with cervical cancer in Isfahan province during 2014-2016. Materials and Methods In this descriptive-analytical study, 77 patients with cervical cancer were selected in Isfahan province. Data were extracted from medical records. Kruskal–Wallis test, one-way analysis, Chi-Square and Mann-Whithney, T test and pearson testwere used for analysis of data. Results In current study, 38.9 ٪ of patients with cervical cancer did not perform Pap smear test during their lifetime. Moreover, 38.09٪ and 19.48٪ of patients performed screening less and more than 3 years before diagnosis, respectively. There was significant relation between screening history with age at diagnosis time, number of pregnancy and age of first sexual intercourse(p<0.01). Statistical analysis showed that the level of education was higher in patients who were diagnosed less than 3 years than those more than 3 years (p=0.04). The frequency of patients who performed screening in urban area was significantly higher than rural area (p=0.048). Moreover, significant difference was observed between provider type screening service in terms of location (p=0.03). Conclusion The result of this study indicates the role of influential factors on Pap smear screening. Moreover, history of not performing Pap smear test in our country in comparison to other countries is high which leads to delay diagnosis. Therefore, general screening program to improve awareness of population in this regard is necessary.